2020
DOI: 10.3892/ol.2020.12422
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑640 promotes cell proliferation and adhesion in glioblastoma by targeting Slit guidance ligand 1

Abstract: The effects of microRNAs (miRNAs/miRs) on glioblastoma have attracted the attention of researchers in the last 7 years. However, the role of miR-640 and its targeted gene, Slit guidance ligand 1 (SLIT1), in the development of glioblastoma are not yet fully understood. The present study aimed to investigate the role of miR-640 in the proliferation and adhesion of glioblastoma. Reverse transcription-quantitative PCR analysis was performed to detect miR-640 and SLIT1 expression in glioblastoma tissues and cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
1
2
Order By: Relevance
“…In this study, we analyzed how SLIT1 affects glioma radiation tolerance. We found that SLIT1 was overexpressed in gliomas, which is inconsistent with the observations reported by Luo et al ( 32 ). The discrepancy could have occurred because our glioma tissue samples were radio-treated, while those used by Luo et al ( 32 ) were not.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, we analyzed how SLIT1 affects glioma radiation tolerance. We found that SLIT1 was overexpressed in gliomas, which is inconsistent with the observations reported by Luo et al ( 32 ). The discrepancy could have occurred because our glioma tissue samples were radio-treated, while those used by Luo et al ( 32 ) were not.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that SLIT1 was overexpressed in gliomas, which is inconsistent with the observations reported by Luo et al ( 32 ). The discrepancy could have occurred because our glioma tissue samples were radio-treated, while those used by Luo et al ( 32 ) were not. In addition, we observed radiation-induced SLIT1 expression and detected SLIT1 silencing-induced radio-sensitization of the tested glioma cell lines.…”
Section: Discussioncontrasting
confidence: 99%
“…Lastly, SLIT1, which is a secreted axon guidance molecule [ 31 ], has substantially downregulated protein and mRNA expression in GBM tissues compared to normal tissues. It is significantly suppressed by miR-640 and consequently stimulates the adhesion and proliferation of GBM cell lines, suggesting that the miR-640/SLIT1 axis might have the potential to act as a novel target for the treatment and diagnosis of GBM [ 32 ].…”
Section: Introductionmentioning
confidence: 99%